Reconfigurative pesantren: Strategic management of value-preserving institutional change in islamic education - Luqman Hadi; Muhammad Amruddin Latif (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Islamic boarding schools (pesantren) in Indonesia are increasingly confronted with simultaneous pressures arising from regulatory expansion, socio-cultural expectations, and digital transformation. While existing studies have largely focused on curriculum modernization and organizational hybridity, limited attention has been given to how value-based pesantren sustain institutional identity while adapting to change. This study aims to examine how Pondok Pesantren Modern Al-Anwar Pacitan reconfigures its institutional structure through the interaction of norms, systems, and leadership agency, and to propose the concept of a “reconfigurative pesantren” as a novel analytical framework. This research employs a qualitative approach using a single instrumental case study design, with data collected through in-depth interviews involving the kiai, director, teachers, students, and guardians, complemented by participatory and non-participatory observations as well as institutional document analysis. Data were analyzed using thematic analysis following Miles et al. (2014) and Braun and Clarke (2006), supported by source, method, and time triangulation. The findings reveal a value-preserving institutional reconfiguration occurring through three interconnected dimensions: normative reconfiguration, where core values are institutionalized into vision, routines, and strategic programs; systemic reconfiguration, reflected in organizational restructuring and selective openness to external pressures; and agency reconfiguration, characterized by delegative-charismatic leadership that distributes authority while maintaining the moral legitimacy of the kiai. The interaction of these dimensions produces a reconfigurative pesantren model. The study concludes that pesantren function as selective and adaptive open systems that strategically transform institutional structures while preserving value continuity, offering a mechanistic explanation of sustainable transformation in value-based educational institutions.